Методика экспериментального исследования тепловых режимов проводников с током методом ТКС - Dmitrichenko, Александр; Chaychits, Николай (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The designed methods of the experimental determination of the temperature of the conductor with running on him alternating current through warm-up factor of the resistance. In base of the methods as one should use to dependencies of the resistance veins of the conductor from the temperature. They are organized experimental studies, confirming validity of the designed methods. Motivated practicability of the use given methods for veins conductor of the small section and hidden wiring